Phenotypic reversion in fas mutants of Arabidopsis thaliana by reintroduction of FAS genes: variable recovery of telomeres with major spatial rearrangements and transcriptional reprogramming of 45S rDNA genes - Pavlištová, Veronika; Dvořáčková, Martina; Jež, Michal; Mozgová, Iva; Mokroš, Petr; Fajkus, Jiří (The Plant journal, 2016)
Arabidopsis thaliana mutants dysfunctional in the evolutionarily conserved protein complex chromatin assembly factor-1 (CAF-1), which deposits the canonical histone H3 variant H3.1 during DNA synthesis-dependent chromatin assembly, display complex phenotypic changes including meristem and growth alterations, sensitivity to DNA-damaging agents, and reduced fertility. We reported previously that mutants in the FAS1 subunit of CAF-1 progressively lose telomere and 45S rDNA repeats. Here we show that multiple aspects of the fas phenotype are recovered immediately on expression of a reintroduced FAS1 allele, and are clearly independent of the recovery of rDNA copy-numbers and telomeres. In reverted lines, 45S rDNA genes are recovered to diverse levels with a strikingly different representation of their variants, and the typical association of nucleolar organizing region 4 with the nucleolus is perturbed. One of 45S rDNA variants (VAR1), which is silenced in wild-type (WT) plants without mutation history (Col-0 WT), dominates the expression pattern, whereas VAR2 is dominant in Col-0 WT plants. We propose an explanation for the variability of telomere and 45S rDNA repeats associated with CAF-1 function, suggesting that the differences in nuclear partitioning and expression of the rDNA variants in fas mutants and their revertants provide a useful experimental system to study genetic and epigenetic factors in gene dosage compensation.
Keywords: rDNA; proteiny huseníčku; chromatin; telomeres; rRNA gene regulation; ribozomální DNA; Chromatin; chromatin assembly; Arabidopsis Proteins; CAF-1; DNA, Ribosomal; Genome, Plant; genom rostlinný; genome instability; Arabidopsis; telomery; Telomere